SINTESIS LAPISAN TIPIS NANOKOMPOSIT TiO2/CNT MENGGUNAKAN METODE SOL-GEL DAN APLIKASINYA UNTUK FOTODEGRADASI ZAT WARNA AZO ORANGE 3R - Rizky Bimanda Sakti; Agus Subagio; Heri Sutanto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
Nanocomposite thin film of TiO2/CNT as a photocatalyst material was synthesized using the sol-gel method with the dispersion of commercial TiO2 Merck in CNT. The crystal structure and nanocomposite thin film morfology of TiO2/CNT were characterized using X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). Sol TiO2 0.3 M was mixed into the sol CNT with mass ratio of CNT:TiO2 was 1:5. Sol TiO2/CNT was sprayed on a glass substrate that was heated at a temperature of 250 oC, then it was heated at the temperature of 450 °C for 60 minutes. Photodegradation was done by dipping the nanocomposite thin film of TiO2/CNT into 100 mL Azo Orange 3R dye sol 10 ppm, then was irradiated using UV light with a wavelength 380 nm. XRD pattern analysis showed that TiO2 has anatase structure with crystallite size at the range from 72-92 nm by using Scherrer equation. SEM image analysis showed that the grains of TiO2 sfreris pattern and was dispersed on CNT. Refluks TiO2/CNT nanocomposite thin film had been able to degrade Azo Orange 3R dye sol for 12 hours until percentage of 98,2% which was much better than the non reflux TiO2/CNT nanocomposite thin film as 97,2% and the TiO2 thin film as 90,9%. Keywords : TiO2, carbon nanotubes, thin film, nanocomposite, photodegradation, Azo Orange 3R dye.